DEMAND VS SUPPLY PROGRAM KESEHATAN REMAJA DI PUSKESMAS TANAH KALIKEDINDING SURABAYA - Kinanty Putri Sarweni; Rachmat Hargono (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Adolescence is a period of transition from children to adulthood. In thetransitional period, adolescents often face very complex and difficult issues totackle on their own. Since 2003, Ministry of Health (Kementerian Kesehatan) has developed a model of health services that is competing with Health Care service for Youth (PKPR). Puskesmas Tanah Kalikedinding has promotive and preventive activities especially related to adolescents. PKPR is certainly basedon every need and demand of teenage cadres around Tanah Kalikedinding area.The purpose of this study is to identify the needs and expectations of adolescentcadres on youth health programs. This research past descriptive research usingqualitative approach. The research subjects consist of peer educator of Rumah Remaja, one of innovative program of Puskesmas Tanah Kalikedinding which referto adolescent reproductive health, Adolescent Posyandu cadres, adolescentcadres in Al-Fitroh Pesantren and UKS cadres at SMAN 19 Surabaya. The number of informants used in this study are 6 persons. Data collection was obtained directly from the study sites using in-depth interview techniques and focus groupdiscussions (FGDs) conducted by researchers with related adolescent peer. The results showed that adolescents need activities that always provide innovation, activities are not only curative but more on activities that are promotive and preventive such as counseling teenage health, education,and socialization.Keyword: adolescent, program, health, need, expectation